Nerve growth factor gene locus explains elevated renal nerve growth factor mRNA in young spontaneously hypertensive rats - Charchar, F J; Kapuscinski, M K; Harrap, S B (Hypertension (Dallas, Tex. 1979), 1998)
Nerve growth factor (NGF) controls the growth of sympathetic nerves and is increased in young spontaneously hypertensive rats (SHR). The NGF gene has been linked genetically with hypertension in the SHR strain and may explain high NGF mRNA levels. To test for genetic linkage between the NGF gene and its expression in vivo, we examined renal NGF mRNA levels in male SHR, control Donryu rats (DRY), and F2 rats derived from SHR and DRY at ages 2, 4, 10, and 20 weeks. Tail-cuff blood pressure was measured at 4, 10, and 20 weeks of age. NGF mRNA levels in SHR (NGF genotype: SS) were higher than those in DRY (NGF genotype: DD) at 2, 4, and 10 weeks of age (P<0.0001) but the same at 20 weeks of age. In the F2 generation, the S allele was associated with significantly (P=0.01) higher renal NGF mRNA levels at 2 weeks of age. Mean NGF mRNA levels fell (P=0.01) with age in F2 rats, and the difference between SS and DD genotype F2 rats diminished at older ages and was not significant. In F2 rats there was a positive correlation between the number of NGF S alleles inherited and tail-cuff pressure (P<0.007). Our findings indicate that the NGF locus is an important regulator of NGF mRNA levels. It is likely that mutations in or near the NGF gene explain in part high early NGF gene expression in SHR.